Neoclassical impurity flux in presence of turbulent generated poloidal asymmetries and pressure anisotropy. (7th March 2019) - Donnel, P; Garbet, X; Sarazin, Y; Grandgirard, V; Bouzat, N; Caschera, E; Dif-Pradalier, G; Ghendrih, P; Gillot, C; Latu, G; Passeron, C
Abstract: Poloidal asymmetries of impurities are commonly observed experimentally. Density asymmetry is already known to impact significantly the neoclassical prediction of impurity fluxes. In this article, the effect of impurity pressure asymmetry and anisotropy on the neoclassical flux of impurity is derived analytically. This prediction is compared with simulations performed with the gyrokinetic code GYSELA, featuring both turbulent and neoclassical transports. A fair agreement is found between the analytical prediction and the result of the simulation. On the special cases which are considered, the effects of impurity pressure asymmetry and anisotropy are shown to play a prominent role in the modification of the neoclassical impurity transport.